Product Diversity And Prices On Repurchase Interest And Consumer Loyalty At Upt Batu Herbal Materia Medica Laboratory - Risca Damayanti Fansia; Ratna Wardani (Journal of Hospital Management and Services, 2019)
Sales of medicinal plant products at the UPT Herbal Materia Medica Laboratory in Batu have decreased in recent months from the desired target, while the growth of producers of similar medicinal plant products has mushroomed in the city of Batu. This research aims to analyze product diversity and product prices on repurchase interest and consumer loyalty at the Batu Medica Herbal Laboratory UPT. This research method is observational with a cross sectional approach. The number of samples taken in this research was determined using a purposive sampling method, namely consumers aged 18 years and over and who made more than one purchase at the herbalmart UPT Batu Herbal Materia Medica Laboratory, namely 32 samples. The data analysis method used is path analysis. From the path analysis results, it was obtained that the value of the direct influence of product prices > the indirect influence value (0.814 > 0.072) so that it was concluded that there was a direct influence of product prices through repurchase interest on consumer loyalty. The results of this research can be contributed as consideration for the UPT Herbal Materia Medica Laboratory in Batu to analyze and evaluate the influence of product diversity, product price on repurchase interest and consumer loyalty.